The Utilization of Chitosan on Fishery Industrial Wastewater Treatment - Bustami Ibrahim; Pipih Suptijah; . Prantommy (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2009)
Highly organic substances contained within fishery industrial wastewater will pollute the environment when it flows into public water body without any previous treatment. Chitosan is polymersubstance extracted from shrimp shell which is able to wrap solid particles suspended in liquids and bring them together and agglomerate makes it suitable as a coagulant aid. The objective of this research was to study the effectiveness of chitosan in order to decrease pollutant parameter in the fishery industrial wastewater. The quality of chitosan used during this research confirmed to Protan Laboratory standard. Results showed that chitosan as a coagulant has good performance in pH range of 6.6-6.8 and at concentration of 175-225 ppm. Within these conditions, chitosan could decrease turbidity value 94.33%-95.17%, TSS (Total Suspended Solids) 95.10%-95.82%, BOD (Biochemical Oxygen Demand) 72.09%-79%, COD (Chemical Oxygen Demand) 76.72%-79.40%, TKN (Total Kjeldahl Nitrogen) 12.50%-27.82%, NH3 80.84%-82.56%, NO2-N 47.69%-54.74%, NO3-N 19.39%-40.14%. The best chitosan concentration to use was at 200 ppm. The quality of effluent produced confirmed to Standard Regulation Indonesian Ministry of Environmental for Standard of Industrial Wastewater no.:KEP-51/MENLH/10/1995.Keywords: chitosan, coagulant, fishery industrial wastewater treatment